Does Calcium Phosphate Cement Kyphoplasty Cause Intervertebral Disk Degeneration in Adolescents?. (December 2022) - Tschauner, Sebastian; Singer, Georg; Weitzer, Claus-Uwe; Castellani, Christoph; Till, Holger; Sorantin, Erich; Wegmann, Helmut
Objective: Balloon kyphoplasty with polymethylmethacrylate (PMMA) represents the standard procedure for the treatment of thoracic and lumbar type A compression fractures. However, an increased degeneration in adjacent intervertebral disks following PMMA kyphoplasty has been demonstrated in elderly patients. Calcium phosphate cement (CPC) appears to be superior to PMMA for the intravertebral stabilization in younger patients. It remains unkown whether CPC kyphoplasty causes degeneration of adjacent disks in adolescents. Design: Seven adolescents with thoracolumbar spine fractures underwent kyphoplasty at a mean age of 14.5 years (range 10-18). At a mean follow-up of 3.7 years (range 1 to 4.8) postoperatively, 3.0 Tesla magnetic resonance imaging (MRI) of the spine was performed to assess intervertebral disk degeneration by quantitative T2 relaxation maps and subjective ratings using modified Pfirrmann scores. A total of 56 intervertebral disks was analyzed. Initial computed tomography (CT) examinations served as basis to assess the severity of adjacent endplate injuries in terms of articular step-offs. Results: Initial imaging detected 18 thoracolumbar vertebral body fractures of which 9 were treated with CPC kyphoplasty. Quantitative follow-up MRI revealed signs of degeneration in 10 (17.9%) of the examined 56 intervertebral disks, 7 of them adjacent to a previously fractured vertebral body. Signs of disk degeneration were significantly higher in caudal endplates with articular step-offs larger than 5 mm compared to fractured vertebral bodies without endplate step-offs. Conclusions: Quantitative MRI follow-ups did not suggest CPC-related intervertebral disk degradations following thoracolumbar kyphoplasty in adolescents, but indicated disk alterations correlating to adjacent endplate fracture severity.